2016
DOI: 10.1007/s00216-016-9525-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals mycoplasma contamination interferes with the metabolism of PANC-1 cells

Abstract: Mycoplasma contamination is a common problem in cell culture and can alter cellular functions. Since cell metabolism is either directly or indirectly involved in every aspect of cell function, it is important to detect changes to the cellular metabolome after mycoplasma infection. In this study, liquid chromatography mass spectrometry (LC/MS)-based metabolomics was used to investigate the effect of mycoplasma contamination on the cellular metabolism of human pancreatic carcinoma cells (PANC-1). Multivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Mycoplasma contamination is a common problem in cell culture and affects many aspects of cell physiology (Kagemann et al 2005a;Yu et al 2016). In this study, we found that mycoplasma contamination could increase the phosphorylation of NF-kB and MAPK signal pathway and induce the activation of BV2 cells.…”
Section: Discussionsupporting
confidence: 54%
“…Mycoplasma contamination is a common problem in cell culture and affects many aspects of cell physiology (Kagemann et al 2005a;Yu et al 2016). In this study, we found that mycoplasma contamination could increase the phosphorylation of NF-kB and MAPK signal pathway and induce the activation of BV2 cells.…”
Section: Discussionsupporting
confidence: 54%
“…The candidate markers were selected by examining the S-plot based on the variable importance (VIP) value, which was more than 1.0. The identification of the metabolites was confirmed by comparisons of fragmentation spectra and m/z through three main online databases: Metlin ( http://metlin.scripps.edu ), HMDB ( http://www.hmdb.ca/ ), and mzcloud ( https://www.mzcloud.org/ ) [ 14 , 15 ]. To assess the strength of association between individual metabolites and minimal/mild endometriosis, a step-wise logistic regression analysis with backward elimination was used to establish a model and filter crucial metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxanthine-guanine phosphoribosyl transferase (HGPRT) and adenine phosphoribosyl transferase (APRT) can convert adenine, hypoxanthine and guanine to adenosine 5′-monophosphate (AMP), inosine 5′-phosphate (IMP) and guanosine 5′-phosphate (GMP), respectively. They are the substrates for the synthesis of high-energy nucleotides and it was reported that AMP and GMP levels were significantly up-regulated in normal gastric tissue from patients with gastric cancer [11,27,28]. In the present study, adenine, hypoxanthine and guanine were significantly upregulated in the chronic gastritis group, which might suggest that the synthesis of AMP, IMP, and GMP was enhanced.…”
Section: Purine Metabolism-supporting
confidence: 51%